Dental trauma in an adolescent - Ledis Sabina Díaz Sánchez; María Isabel Jiménez Castellanos; Delvis Páez Delgado (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 15 year-old patient is described who as a result of a trauma, suffered intrusive luxation of the 12 and lateral of the 11 with loss of vitality of both teeth. She received immediate treatment in the emergency room with slow course and due to other clinical manifestations she visited the Comprehensive General Stomatology  service of Mártires del Moncada Teaching Provincial Stomatological Clinic inSantiago de Cuba.   Endodontic treatment was carried out in both teeth and it was referred to the  Orthodontics  service where fixed aparatology was placed up to achieving a functional resalte y sobrepase.